THE RELATIONSHIP BETWEEN PROLONGED STANDING AND HALLUX VALGUS IN SALESPERSON - Pratiwi, Galuh Aullia; Winaya, I Made Niko; Primayanti, Dewa Ayu Inten (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRAK Hallux valgus is a condition if first metatarsal medial deviation and thumb or hallux lateral deviation and rotation. Factor that affected was the prolonged standing use of constrictive footwear such as high-heeled shoes. Prolonged standing was standing with  more than 4 hours per day.This study was cross sectional analytic observation and 62 female salesperson who worked in Mall X were selected to be sample. Measuring instruments used to determine the hallux valgus was using the Manchester scale. This study was shown there wes a significant relationship between prolonged standing and hallux valgus in female salesperson p = 0.007 (p <0.05). From 62 female salesperson, the were 46 who had hallux valgus, in which 43 persons worked with longterm standing (93.5%) and 3 persons (6.5%) worked without longterm standing. However, from 16 salesperson who had not hallux valgus, there was 10 persons (62.5%) worked with longterm standing and 6 persons worked without longterm. Key w ords : Hallux valgus, Prolonged standing, salesperson